Theoretical exploration of the optoelectronic properties of InAsNBi/InAs heterostructures for infrared applications: A multi-band k·p approach. (September 2022) - Jain, Neelesh; Mal, Indranil; Samajdar, D.P.; Bagga, Navjeet
Abstract: We have investigated numerous electronic and optical aspects of the InAsNBi material, considering a multi-band k·p Hamiltonian. We have scrutinised electronic band dispersion, changes in spin–orbit splitting energy (so), charge carrier effective mass, band offset, and optical gain variations of InAsNBi and Quantum Well (QW) structures lattice-matched to InAs. The band gap of InAs0.9209 N0.0291 Bi0.05 is observed to be 131 meV under lattice-matched conditions, and the operating wavelength equivalent to this bandgap is 9.46 μm, which corresponds to the atmospheric Long Wavelength Infrared (LWIR) communication window of 8–12 μm. In order to tune the bandgap of a quantum confined heterostructure over a wide range, strain analysis plays a pivotal role. While compressive strain of 0.7% offers a band gap of 96 meV, tensile strain of 1.16% generates a band gap to 178 meV, which is almost equivalent to the room temperature bandgap of InSb. Under the influence of strain, spin-orbit splitting energy (Δso ) spans the range from 0.31 eV to 0.45 eV. In addition to this, the inclusion of N and Bi into InAs reduces the effective mass of electrons to 0.01343 m0, which is ∼0.5 times of InAs. We have also computed the band structure of the InAsNBi/InAs QW heterostructure and found that under the influence of tensile strain with N = 2.5% and Bi = 1%, there is a changeover from Type-I to Type-II heterostructure. Indeed, InAsNBi can be a potential material for realizing various optoelectronic applications such as atmospheric LWIR communication, intermediate band solar cells, and night vision cameras.